The therapeutic potential of low-intensity focused ultrasound for treating substance use disorder - Olaitan, Greatness O.; Lynch, Wendy J.; Venton, B. Jill (Frontiers in Psychiatry, 2024)
Substance use disorder (SUD) is a persistent public health issue that necessitates the exploration of novel therapeutic interventions. Low-intensity focused ultrasound (LIFU) is a promising modality for precise and invasive modulation of brain activity, capable of redefining the landscape of SUD treatment. The review overviews effective LIFU neuromodulatory parameters and molecular mechanisms, focusing on the modulation of reward pathways in key brain regions in animal and human models. Integration of LIFU with established therapeutics holds promise for augmenting treatment outcomes in SUD. The current research examines LIFU's efficacy in reducing cravings and withdrawal symptoms. LIFU shows promise for reducing cravings, modulating reward circuitry, and addressing interoceptive dysregulation and emotional distress.Selecting optimal parameters, encompassing frequency, burst patterns, and intensity, is pivotal for balancing therapeutic efficacy and safety. However, inconsistencies in empirical findings warrant further research on optimal treatment parameters, physiological action mechanisms, and long-term effects. Collaborative interdisciplinary investigations are imperative to fully realize LIFU's potential in revolutionizing SUD treatment paradigms and enhancing patient outcomes.